2019
DOI: 10.1074/jbc.ac118.007143
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoglycolate phosphatase is a metabolic proofreading enzyme essential for cellular function in Plasmodium berghei

Abstract: Edited by Ruma BanerjeePlasmodium falciparum (Pf) 4-nitrophenylphosphatase has been shown previously to be involved in vitamin B1 metabolism. Here, conducting a BLASTp search, we found that 4-nitrophenylphosphatase from Pf has significant homology with phosphoglycolate phosphatase (PGP) from mouse, human, and yeast, prompting us to reinvestigate the biochemical properties of the Plasmodium enzyme. Because the recombinant PfPGP enzyme is insoluble, we performed an extended substrate screen and extensive biochem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interestingly, a recent study suggested that the P. berghei PGP selectively utilized 2-phospho- l -lactate over 2-phospho- d -lactate in vitro (15), raising the possibility that this enzyme acts on both enantiomers in vivo depending on their intracellular concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study suggested that the P. berghei PGP selectively utilized 2-phospho- l -lactate over 2-phospho- d -lactate in vitro (15), raising the possibility that this enzyme acts on both enantiomers in vivo depending on their intracellular concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…falciparum dephosphorylates a range of metabolites, including thiamine pyrophosphate, and its homolog in P. berghei was reported to be essential for regulating 2-phosphoglycolate and 2-phospholactate levels (15, 16). Here, we establish in P.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the possibility that 2-phosphoglycolate, 4-phosphoerythronate and 2-phospholactate serve as 'physiological' substrates for PGP/G3PP is remote, unlike glycerol-3-phosphate, which is present at above its Km concentration in cells normally, and is readily available as substrate for G3PP. However, as 4-phosphoerythronate and 2phospholactate accumulate when PGP expression is suppressed (32)(33)(34), the possibility that PGP/G3PP may act on these substrates with very low efficiency due to their extremely low intracellular concentrations, cannot be discounted. Even though purified recombinant mouse PGP was found to show high catalytic efficiency with 2-phosphoglycolate, 4phosphoerythronate, and 2-phospholactate, and relatively lower activity with Gro3P (22,32), it also shows very high activity with the non-physiological substrate p-nitrophenol phosphate (30).…”
Section: Mammalian Pgp: Names Substrate Specificity and Enzyme Kineticsmentioning
confidence: 99%